2020
DOI: 10.1177/0706743720952234
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care and Access to Mental Health Consultations among Immigrants and Nonimmigrants with Mood or Anxiety Disorders: Soins de première ligne et accès aux consultations en santé mentale chez les immigrants et les non-immigrants souffrant de troubles de l’humeur ou anxieux

Abstract: Objective: To examine the association between usual place of primary care and mental health consultation among those with self-reported mood or anxiety disorders. We also describe access to mental health services among people who are recent immigrants, longer-term immigrants, and nonimmigrants and determine whether the association with place of primary care differs by immigration group. Methods: We used data from the Canadian Community Health Survey (2015 to 2016) to identify a representative sample of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A detailed explanation of the complete CCHS survey methodology and protocol can be found elsewhere ( Statistics Canada, 2018 ). Consistent with prior research ( Rivera et al, 2021 ), the present study only included respondents who reported having been diagnosed with a mood and/or anxiety disorder ( n = 31,485). Because many racialized immigrants coming from low-income and middle-income countries have diverse ethnocultural perceptions of old age ( Lin, 2021 ), the sample in this analysis was further restricted to participants aged 45 and older ( n = 17,644).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed explanation of the complete CCHS survey methodology and protocol can be found elsewhere ( Statistics Canada, 2018 ). Consistent with prior research ( Rivera et al, 2021 ), the present study only included respondents who reported having been diagnosed with a mood and/or anxiety disorder ( n = 31,485). Because many racialized immigrants coming from low-income and middle-income countries have diverse ethnocultural perceptions of old age ( Lin, 2021 ), the sample in this analysis was further restricted to participants aged 45 and older ( n = 17,644).…”
Section: Methodsmentioning
confidence: 99%
“…(e.g., face-to-face or telephone contact).” Previous studies have found that highly distressed individuals may overreport the number of visits compared to administrative records ( Rhodes & Fung, 2004 ). Hence, to lower the risk of recall bias, an aggregated coding (e.g., ever/never) was used for past-year MHC ( Rivera et al, 2021 ). Frequency of visits (mean) was only presented for descriptive purpose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to focus on having any visit within the year rather than visit volume as a marker of any contact with primary care. This is particularly important in the context of the pandemic, given the potential for people to have lost contact with healthcare, and who may lack a regular place of care or first point of access (34,35).…”
Section: Methodsmentioning
confidence: 99%